Implementation of Philosophical Values on Islamic Religious Education Learning in Pondok Darul Fikri, Indonesia - Rahmawati, Din Silmi; Ikhwan, Afiful (Universitas Muhammadiyah Yogyakarta, 2025)
Philosophical values in Islamic Religious Education (PAI) learning are one way to shape students' character and spiritual awareness. This article discusses how philosophical values such as sincerity, responsibility, justice, and patience can be instilled through a dialogic and reflective Islamic Education learning process. This study aims to determine the teacher's strategy in building students' value awareness and how the boarding school environment supports the process. This research used qualitative methods with data collection techniques such as observation, interviews, and documentation at Darul Fikri Islamic Boarding School. The novelty of this study lies in integrating reflective learning and character building through the tahfidz program as a contextual and practical means of internalizing philosophical values in the pesantren environment, which has not been widely studied in previous research. The results showed that PAI learning integrated with philosophical values through discussion methods, reflective assignments, and habituation in the Qur'an tahfidz program, greatly helped students form better attitudes and behaviors. Santri can reflect on religious teachings more deeply and apply them in everyday life. With the right approach, philosophical values can be instilled effectively and have a real impact on the character-building process of students.